On the Mechanism of Polyuria in Potassium Depletion: THE ROLE OF POLYDIPSIA - Berl, Tomas (1977)
The association of potassium (K) depletion with polyuria and a concentrating defect is established, but the extent to which these defects could be secondary to an effect of low K on water intake has not been systematically investigated. To determine whether hypokalemia has a primary effect to increase thirst and whether any resultant polyuria and polydipsia contribute to the concentrating defect, we studied three groups of rats kept in metabolic cages for 15 days. The groups were set up as follows: group 1, normal diets and ad lib. fluids (n = 12); group 2, K-deficient diet on ad lib. fluids (n = 12); and group 3, K-deficient diet and fluid intake matched to group 1 (n = 14). Daily urine flow and urinary osmolality of groups 1 and 3 were not significantly different throughout the study. In contrast, as of day 6, group 2 rats consistently had a higher fluid intake (P < 0.0025), higher urine flow (P < 0.001), and lower urinary osmolality (P < 0.001) than the other two groups. These alterations in fluid intake and urine flow preceded a defect in maximal concentrating ability. On day 7, maximal urinary osmolality was 2,599±138 msmol/kg in rats on K-deficient intake and 2,567±142 msmol/kg in controls. To determine whether this primary polydipsia is itself responsible for the development of the concentrating defect, the three groups of rats were dehydrated on day 15. Despite different levels of fluid intake, maximal urinary osmolality was impaired equally in groups 2 and 3 (1,703 and 1,511 msmol/kg, respectively), as compared to rats in group 1 (2,414 msmol/kg), P < 0.001. We therefore conclude that K depletion stimulates thirst, and the resultant increase in water intake is largely responsible for the observed polyuria. After 15 days of a K-deficient diet, the impaired maximal urinary concentration in hypokalemia, however, was not related to increased water intake, since fluid restriction did not abolish the renal concentrating defect.